The analysis of progress CSR good practices areas in logistic companies based on reports “Responsible Business in Poland. Good Practices” in 2010-2014 - Katarzyna TUROŃ; Dagmara GOLBA; Piotr CZECH (Scientific Journal of Silesian University of Technology. Series Transport)
The article presented the analysis of progress CSR good practices areas in logistic companies. Authors considered areas of good practices, which were reported by DB Schenker and Raben Group to “Responsible Business in Poland. Good Practices” from 2010 to 2014. The authors also verified the occurrence of niche in logistic CSR areas, which could be used by the other companies that starts their CSR activities.